The effectiveness of local wisdom based science and social teaching materials on character development: a pre-experimental study - Ila Susilawati; Yayat Hidayat; Eka Nurhidayat; Aji Septiaji; Devi Afriyuni Yonanda (Jurnal Bidang Pendidikan Dasar, 2026)
The integration of local wisdom into elementary IPAS (science and social studies) learning remains limited, resulting in less contextual instruction and weaker support for character development. This study examined the effectiveness of Local Wisdom–Based IPAS teaching materials in improving fourth-grade students’ conceptual understanding and character. A pre-experimental one-group pretest–posttest design was conducted with 30 students. Data were collected through conceptual understanding tests and character assessment instruments. Results showed a significant improvement in learning outcomes, with mean scores increasing from 74.33 to 81.30 (p < 0.05) and a large effect size (Cohen’s d = 1.29). Shapiro–Wilk tests confirmed normal data distribution (pretest p = 0.150; posttest p = 0.081). The findings indicate that activating prior knowledge rooted in local wisdom, supported by culturally responsive and multimodal learning approaches, promotes meaningful learning. This study provides empirical evidence that local wisdom–based materials enhance both academic achievement and character development in elementary education.